The Richness and Diversity of Catalases in Bacteria - Yuan, Fang; Yin, Shouliang; Xu, Yang; Xiang, Lijun; Wang, Haiyan; Li, Zilong; Fan, Keqiang; Pan, Guohui (Frontiers in Microbiology, 2021)
Catalases play a key role in the defense against oxidative stress in bacteria by catalyzing the decomposition of H2O2. In addition, catalases are also involved in multiple cellular processes, such as cell development and differentiation, as well as metabolite production. However, little is known about the abundance, diversity and distribution of catalases in bacteria. In this study, we systematically surveyed and classified the homologs of three catalase families from 2,634 bacterial genomes. It was found that both of the typical catalase and Mn-catalase families could be divided into distinct groups, while the catalase-peroxidase homologs formed a tight family. The typical catalases are rich in all the analyzed bacterial phyla except Chlorobi, in which the catalase-peroxidases are dominant. Catalase-peroxidases are rich in many phyla, but lacking in Deinococcus-Thermus, Spirochaetes and Firmicutes. Mn-catalases are found mainly in Firmicutes and Deinococcus-Thermus, but are rare in many other phyla. Given the fact that catalases were reported to be involved in secondary metabolite biosynthesis in several Streptomyces strains, the distribution of catalases in the genus Streptomyces was paid more attention herein. On average, there are 2.99 typical catalases and 0.99 catalase-peroxidases in each Streptomyces genome, while no Mn-catalases were identified. To understand detailed properties of catalase in Streptomyces, we characterized all the five typical catalases from S. rimosus ATCC 10970, the oxytetracycline producing strain. The five catalases showed typical catalase activity, but possessed different catalytic properties. Our findings contribute to the more detailed classification of catalases and facilitate further studies about their physiological roles in secondary metabolite biosynthesis and other cellular processes, which might facilitate the yield improvement of valuable secondary metabolites in bacteria.